Consensus statement on prevention and detection of ovarian hyperstimulation syndrome. (24th November 2015) - Boothroyd, Clare; Karia, Sonal; Andreadis, Natasha; Rombauts, Luk; Johnson, Neil; Chapman, Michael; ,
Abstract : Background: Ovarian hyperstimulation syndrome is an important condition with considerable morbidity and a small risk of mortality, which most commonly results as an iatrogenic condition following follicular stimulation of the ovaries. Aim: To produce evidence‐based and consensus statements on the prevention and detection of ovarian hyperstimulation syndrome (OHSS). Method: The CREI Consensus Group met in 2008 and identified issues for inclusion and review. Review of the available evidence was conducted and consensus statements prepared. Areas of dissent of expert opinion and for further research were noted. Results: The group considered that there is a need for standardisation of the definition and classification of the clinical syndrome of OHSS to allow further conclusive research. Interventions with evidence of effect in reducing OHSS include the use of metformin in women with PCOS, use of GnRH antagonist rather than GnRH agonist and use of GnRH agonist triggers in GnRH antagonist stimulation cycles. The consensus view was that reducing the dose of FSH, freezing all embryos and transferring a single embryo were appropriate interventions to reduce OHSS. Agreement could not be reached on coasting, the lowest number of oocytes to consider freezing all embryos and management after cancellation of oocyte collection. Conclusion: OHSS is a serious condition for which there are a number of proven preventative strategies. OHSS is an area requiring ongoing research and development of a universally agreed definition will allow development of optimal prevention strategies and facilitate improved early detection of women at risk.